EFEKTIFITAS PEMBELAJARAN MENGGUNAKAN MEDIA AUDIO–VISUAL TERHADAP TEKNIK PASSING DALAM SEPAK BOLA UNTUK KELAS X.KA1 SMKN 5 SURABAYA (STUDI PADA SISWA KELAS X.KA1 SMKN 5 SURABAYA TAHUN AJARAN 2011-2012) - MARIANO ANUGERANTO, VIANEY (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The utilization of media on learning process able to facilitate student on matter absorption. Especially through picture since it can be see visually by student. Picture media can smooth the achievement of goal to comprehend and memorizing information or message that contained on picture. Based on observation of teacher, that football learning especially on passing, student is lack of comprehension, therefore learning by using audio visual media expected able to facilitate student to understand passing technique on football.   Keywords: Physical education sport and health, teacher professionalism, student learning result.